Hepatic cystic echinococcosis (type II): A case report - Zhiru Liang; Weihong Chen; Binbin Zhang; Lina Chen; Jing Wang; Jianjia Xiao; Geer An (Journal of International Medical Research)
This article presents a case report of a rare instance of hepatic cystic echinococcosis (Type II). The patient is a young female who has resided in the Inner Mongolia region of China for an extended period and has a clear history of contact with dogs and sheep. She presented with recurrent upper abdominal pain accompanied by jaundice of skin and sclera for 2 months. Through comprehensive clinical history inquiry, physical examination, and imaging studies such as ultrasound and computed tomography, the diagnosis of hepatic cystic echinococcosis (Type II) was confirmed. The patient underwent a capsular excision, and the postoperative prognosis was good with no recurrence or implantation during short-term follow-up. This case report details the patient’s clinical symptoms, signs, diagnostic process, and key points for differential diagnosis, emphasizing the crucial role of imaging studies in the diagnosis of hepatic cystic echinococcosis. Additionally, the treatment plan and postoperative follow-up for this case are discussed, aiming to provide a reference for clinical diagnosis and treatment of hepatic cystic echinococcosis.